LEXICAL-SEMANTICAL PECULIARITIES OF POLISH LANGUAGE ADVERTISING TEXT AT THE BEGINNING OF THE XXth CENTURY - Pelekhata, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article analyzes the lexical-semantic peculiarities of advertising on the pages of the newspaper «Kurier Stanisławowski», depending on the cultural-historical situation in the period of the formation of massive newest communications. The lexical-semanticfield «Beauty, health, fashion and resttime of the city inhabitants» is separated. Manipulative approaches in advertising texts are analyzed.